International Perspectives on the Covariation Among Adolescent Risk Behaviors - Bo, Ai; Jaccard, James (Journal of adolescent health, 2025)
Characterizations of the magnitude of the correlations between adolescent risk behaviors vary considerably. This study documented correlations between selected risk behaviors (smoking, alcohol use, cannabis use, physical fighting, sexual intercourse, and suicide ideation/attempt) among youth aged 13 to 15 in 125 countries. Country-level indicators such as wealth, income inequality, health and education expenditures, and level of democracy were analyzed to explore predictors of correlation magnitude across countries. Data on adolescent risk behaviors were analyzed from the Global School–based Student Health Survey and the Health Behavior in School-aged Children survey (N = 343,652). Country-level indicators were sourced from databases such as the World Bank DataBank. Risk behaviors (past 30 days or past 12 months) were measured as both dichotomous and count variables. Meta-regression with robust variance estimation and random effects model was used to estimate average correlations across countries and to analyze country-level predictors. The average correlation between dichotomously measured risk behaviors was 0.19, and 0.23 for count outcomes. The highest correlations, around 0.36, were between alcohol use and cigarette smoking. Meta-regression revealed modest relationships between country ecologies and the degree of covariation between risk behaviors. Cluster analysis identified four country profiles based on the country-level indicators with risk behavior average correlations ranging from 0.15 to 0.24 across clusters. Although correlations between risk behaviors exist, their magnitude is modest across 125 countries. These findings suggest that risk behaviors share more unique than common variance. Effective prevention programs should address both common and unique determinants of each risk behavior.